2022
DOI: 10.1145/3510029
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Framework for Modeling Biobehavioral Rhythms from Mobile and Wearable Data Streams

Abstract: This paper presents a computational framework for modeling biobehavioral rhythms - the repeating cycles of physiological, psychological, social, and environmental events - from mobile and wearable data streams. The framework incorporates four main components: mobile data processing, rhythm discovery, rhythm modeling, and machine learning. We evaluate the framework with two case studies using datasets of smartphone, Fitbit, and OURA smart ring to evaluate the framework’s ability to (1) detect cyclic biobehavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…This finding highlights the need for empirical investigation of the threshold while using the Stable FS approach. This finding also extends the previous studies which used random thresholds of 0.25 [47] and 0.75 [48] to select features for depression identification and also in other contexts (e.g., [72] used a threshold of 0.90 in neurobehavioral symptoms identification). While comparing the FS approaches, we found that to achieve the same performance (precision=73.1%, sensitivity 74.5%) of an ML model developed using around 5 features selected by Boruta, we needed 6, 9, and around 14 features of the filter, wrapper, and Stable approaches respectively.…”
Section: The Implication Of the Findingssupporting
confidence: 85%
See 1 more Smart Citation
“…This finding highlights the need for empirical investigation of the threshold while using the Stable FS approach. This finding also extends the previous studies which used random thresholds of 0.25 [47] and 0.75 [48] to select features for depression identification and also in other contexts (e.g., [72] used a threshold of 0.90 in neurobehavioral symptoms identification). While comparing the FS approaches, we found that to achieve the same performance (precision=73.1%, sensitivity 74.5%) of an ML model developed using around 5 features selected by Boruta, we needed 6, 9, and around 14 features of the filter, wrapper, and Stable approaches respectively.…”
Section: The Implication Of the Findingssupporting
confidence: 85%
“…We created 1000 bootstrapped subsamples and used a Logistic Regression classifier as the base estimator which fit on the bootstrapped subsamples. In previous studies of depression identification, researchers used random thresholds (e.g., 0.25 [47], 0.75 [48]) to select the features. Since there is no evidence of getting optimal performance using those thresholds only, in our study, we did an empirical investigation to present the optimal threshold.…”
Section: Feature Selectionmentioning
confidence: 99%
“…Although a recent study extracted parametric rhythmic feature–dominant periods from smartphone usage data [ 32 ], the study was limited by not exploring rhythmic features, such as the acrophase, interdaily stability (IS), intradaily variability (IV), and relative amplitude (RA). In addition, the study explored mere screen usage, without any exploration of more informative features [ 33 ], such as entropy data–based features.…”
Section: Introductionmentioning
confidence: 99%
“…In human life, physiological changes reappear in a cyclable waveform [ 38 ]. Rhythm features based on physiological data have been explored in both the chronobiology [ 39 ] and pervasive health [ 32 ] areas. Researchers have found a relation between physiological data–based rhythmic markers and health status [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation